Tumor suppressor IRF-1 mediates retinoid and interferon anticancer signaling to death ligand TRAIL - Clarke, Nicole (Nature Publishing Group, 2004)
Retinoids and interferons are signaling molecules with pronounced anticancer activity. We show that in both acute promyelocytic leukemia and breast cancer cells the retinoic acid (RA) and interferon signaling pathways converge on the promoter of the tumoricidal death ligand TRAIL. Promoter mapping, chromatin immunoprecipitation and RNA interference reveal that retinoid-induced interferon regulatory factor-1 (IRF-1), a tumor suppressor, is critically required for TRAIL induction by both RA and IFNγ. Exposure of breast cancer cells to both antitumor agents results in enhanced TRAIL promoter occupancy by IRF-1 and coactivator recruitment, leading to strong histone acetylation and synergistic induction of TRAIL expression. In coculture experiments, pre-exposure of breast cancer cells to RA and IFNγ induced a dramatic TRAIL-dependent apoptosis in heterologous cancer cells in a paracrine mode of action, while normal cells were not affected. Our results identify a novel TRAIL-mediated tumor suppressor activity of IRF-1 and suggest a mechanistic basis for the synergistic antitumor activities of certain retinoids and interferons. These data argue for combination therapies that activate the TRAIL pathway to eradicate tumor cells.